Formation of 1,5-Disubstituted 2-hydroxypyrroles via Reaction of 2-(Triphenylphosphoranylidene) succinic Anhydride with Schiff's Bases - Obaid H. Abid; Omar G. Mahdy (مجلة جامعة الانبار للعلوم الصرفة, 2018)
Schiff's Bases were synthesized from the reaction of furfuraldehyde and substituted benzaldehyde with 4-aminoantipyrine and 2,4-dinitrophenylhydrazine and reacted with 2-(triphenylphosphoranylidene) succinic anhydride in an anhydrous 1,4- dioxane at reflux conditions. The resulting products were found to be 1,5-disubstituted 2-hydroxypyrroles. The structures of the products were confirmed by their melting points, FT-IR, 1HNMR spectra and C.H.N. elemental analyses.